Comparative study of the sustainable preparation of FeMn thin films via electrodeposition and magnetron co-sputtering - Fernandez-Barcia, Monica; Kurdi, Samer; Terzopoulou, Anastasia; Barber, Zoe H.; Hoffmann, Volker; Damm, Christine; Giebeler, Lars; Pane, Salvador; Uhlemann, Margitta; Wolf, Ulrike; Nielsch, Kornelius; Gebert, Annett (Surface & Coatings Technology, 2019)
Biodegradable electronic devices based on non-toxic materials are an emerging field, in which the key characteristic is the complete dissolution of the devices within a determined period of time. Usually, these devices are built on polymer substrates or pure metals; however they present some disadvantages such as low degradation rate. The present study reports and compares the sustainable preparation of FeMn films via electrodeposition and magnetron co-sputtering as a possible alternative to the aforementioned materials. Morphological, chemical, structural and magnetic characterization of the obtained layers was carried out and the corrosion and biocompatibility characteristics were assessed by electrochemical studies and cell viability assays. Different ratios of Mn2+:Fe2+ ions in the electrolyte leaded to metallic and oxide based FeMn layers. The electrodeposited FeMn films showed different crystalline structure depending on their nature: a bcc-Fe crystal structure when they are metallic and fcc when they are oxidized. In addition, glycine was used as complexing agent in the electrolytic bath, which leaded to less-crack films and varied the Mn content in the films (9–24 wt%). The Mn content of the magnetron co-sputtered films varied between 10 and 70 wt%. Differently to the electrodeposited films, the sputtered revealed a well-defined bcc structure that lowers its symmetry when the Mn content increases. Regarding the magnetic behavior, all obtained films showed a soft magnetic behavior. Their corrosion behavior in NaCl solutions was evaluated by electrochemical studies, observing a shift to more negative corrosion potential values when Mn content increases. In vitro cytotoxicity tests revealed highly biocompatible characteristics with a cell viability of 85% even for the Mn-richest sputtered films (70 wt%) while electrodeposited films showed a clear indication of toxicity.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Corrosion; Cytotoxicity test; Electrodeposition; FeMn alloys; Magnetron co-sputtering; Thin films